Standards-Based Accountability Under No Child Left Behind Experiences of Teachers and Administrators in Three States - Hamilton, Laura S. (RAND Corporation, 2007)
Since 2001-2002, standards-based accountability provisions of the No Child Left Behind Act of 2001 have shaped the work of public school teachers and administrators in the United States. This book sheds light on how accountability policies have been translated into actions at the district, school, and classroom levels in three states.